IMPLEMENTATION OF ENGINEERING PRODUCT DESIGN FOR SMALL-SCALED MECHANICAL WORKSHOP : A STUDY IN PURBALINGGA, CENTRAL JAVA, INDONESIA - Waluyo, Sugeng; Krisnawati, Maria; Uletika, Niko Siameva (Techno Jurnal Ilmu Teknik, 2015)
Engineering product design can be understood simply as a collection of engineering activities that must be followed to produce good industrial products. In the simplest form it can be constructed from three major stages, i.e. specification of design requirements, drawing and prototyping.In order to give an overview of its implementation related to small-scaled mechanical workshop a prototype of plate bending machine is built completely from its design requirements. The machine is considered important because it supports standard manufacturing processes, i.e. plate forming, of muffler industries in Purbalingga, Central Java, Indonesia. During prototyping, communication among designer, drafter and manufacturer has been identified as the major responsible factor for producing design errors on the machine for each the stages. Thus, the proposed strategies, e.g. implementation of engineering software design and development of engineering design center in university, to minimize them based on quantitative approach are briefly discussed as well.Keywords : engineering design, prototype, bending machine, Purbalingga